TIME-RESOLVED SYNCHROTRON X-RAY COMPUTED TOMOGRAPHY AS A TOOL FOR GROUNDWATERE REMEDIATION - LOPES ARCHILHA, NATHALY; SCHUBERT RUIZ COSTA, GABRIEL; PAK, TANNAZ (Águas Subterrâneas, 2021)
Time-resolved X-ray microtomography is a cutting-edge techinque that enables the study of dynamic events, such as sample deformation, mineral reaction and fluid migration through real samples. For the first time, it is now possible to identify and quantify pore scale events, in real time, and correlate them to macroscales behaviours of the system. The goal of this work is to provide illustrative examples of what is achievable with this technique applied to fluid flow in porous media, more specifically, groundwater remediation. This technique is already available at the Imaging Beamline (IMX) from the Brazilian Synchrotron Light Source, but at SIRIUS, the new Light Source that Brazil is building in Campinas/São Paulo, a new beamline will be open for the community, which will provide better measurements in terms of timescales and spatial resolution.